Development of Effective Lipase-Hybrid Nanoflowers Enriched with Carbon and Magnetic Nanomaterials for Biocatalytic Transformations - Renia Fotiadou; Michaela Patila; Mohamed Amen Hammami; Apostolos Enotiadis; Dimitrios Moschovas; Kyriaki Tsirka; Konstantinos Spyrou; Emmanuel P. Giannelis; Apostolos Avgeropoulos; Alkiviadis Paipetis; Dimitrios Gournis; Haralambos Stamatis (Nanomaterials, 2019)
In the present study, hybrid nanoflowers (HNFs) based on copper (II) or manganese (II) ions were prepared by a simple method and used as nanosupports for the development of effective nanobiocatalysts through the immobilization of lipase B from Pseudozyma antarctica. The hybrid nanobiocatalysts were characterized by various techniques including scanning electron microscopy (SEM), energy dispersion spectroscopy (EDS), X-ray diffraction (XRD), Raman spectroscopy, and Fourier transform infrared spectroscopy (FTIR). The effect of the addition of carbon-based nanomaterials, namely graphene oxide and carbon nanotubes, as well as magnetic nanoparticles such as maghemite, on the structure, catalytic activity, and operational stability of the hybrid nanobiocatalysts was also investigated. In all cases, the addition of nanomaterials during the preparation of HNFs increased the catalytic activity and the operational stability of the immobilized biocatalyst. Lipase-based magnetic nanoflowers were effectively applied for the synthesis of tyrosol esters in non-aqueous media, such as organic solvents, ionic liquids, and environmental friendly deep eutectic solvents. In such media, the immobilized lipase preserved almost 100% of its initial activity after eight successive catalytic cycles, indicating that these hybrid magnetic nanoflowers can be applied for the development of efficient nanobiocatalytic systems.